Didepside Formation by the Nonreducing Polyketide Synthase Preu6 of Preussia isomera Requires Interaction of Starter Acyl Transferase and Thioesterase Domains. Issue 6 (29th December 2022) - Liu, Qingpei; Zhang, Dan; Gao, Shuaibiao; Cai, Xianhua; Yao, Ming; Xu, Yao; Gong, Yifu; Zheng, Ke; Mao, Yigui; Yang, Liyan; Yang, Dengfeng; Molnár, István; et al.
Abstract: Orsellinic acid (OA) derivatives are produced by filamentous fungi using nonreducing polyketide synthases (nrPKSs). The chain‐releasing thioesterase (TE) domains of such nrPKSs were proposed to also catalyze dimerization to yield didepsides, such as lecanoric acid. Here, we use combinatorial domain exchanges, domain dissections and reconstitutions to reveal that the TE domain of the lecanoric acid synthase Preu6 of Preussia isomera must collaborate with the starter acyl transferase (SAT) domain from the same nrPKS. We show that artificial SAT‐TE fusion proteins are highly effective catalysts and reprogram the ketide homologation chassis to form didepsides. We also demonstrate that dissected SAT and TE domains of Preu6 physically interact, and SAT and TE domains of OA‐synthesizing nrPKSs may co‐evolve. Our work highlights an unexpected domain–domain interaction in nrPKSs that must be considered for the combinatorial biosynthesis of unnatural didepsides, depsidones, and diphenyl ethers. Abstract : Ester‐bond‐forming dimerization to afford the didepside lecanoric acid is shown to require both the starter acyltransferase and the thioesterase domains of the nonreducing polyketide synthase Preu6 of the fungus Preussia isomera . These domains also engage in an unexpected, direct protein–protein interaction that must be considered when attempting combinatorial biosynthesis of unnatural didepsides, depsidones, and diphenyl ethers.